STUDI SIFAT MEKANIK KOMPOSIT SERAT SANSEVIERIA CYLINDRICA DENGAN VARIASI FRAKSI VOLUME BERMATRIK POLYESTER - Fajri, Rahmat Iskandar; Tarkono, .; Sugiyanto, . (FT UNILA, 2013)
This study aims to create and analyze the tensile strength of the material matrix composite reinforced polyester resin natural fiber Sansevieria cylindrica leaves that will eventually be in seek of new composite materials which might be expected to be a reference material that is environmentally friendly. The results showed an increase in tensile strength of the composite fiber volume fraction of each additional up to 20%. At 10% fiber volume fraction values obtained 18.459N/mm2, then power up the volume fraction of 20% to reach a value 45.698N/mm2, but declining power back on composite with 30% fiber volume fraction is 32.891N/mm2. From microstructure observations made by SEM photo can be seen in the composite fiber distributionuneven in some parts of the composite fiber reinforcing material contained gaps, so that part hasthe tensile strength values are different.Keywords: composite, composite tensile strength, static tensile strength fibers, Sansevieriacylindrica.